2013
DOI: 10.1038/cddis.2013.469
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide induces apoptosis in human leukemia cells through caspase-3-mediated ROCK1 activation and MLC phosphorylation

et al.

Abstract: The diterpene triepoxide triptolide is a major active component of Tripterygium wilfordii Hook F, a popular Chinese herbal medicine with the potential to treat hematologic malignancies. In this study, we investigated the roles of triptolide in apoptosis and cell signaling events in human leukemia cell lines and primary human leukemia blasts. Triptolide selectively induced caspase-dependent cell death that was accompanied by the loss of mitochondrial membrane potential, cytochrome c release, and Bax translocati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 46 publications
(65 reference statements)
1
21
0
Order By: Relevance
“…The active fraction have inhibited cell proliferation greatly through reducing yellow color tetrazolium salt in to a dark blue/purple product of cellular mitochondrial dehydrogenase enzyme in living cells . Inhibition of cytosolic compartment of cell proliferation at different time‐point in renal carcinoma cells were in accordance with previous reports .…”
Section: Resultssupporting
confidence: 91%
“…The active fraction have inhibited cell proliferation greatly through reducing yellow color tetrazolium salt in to a dark blue/purple product of cellular mitochondrial dehydrogenase enzyme in living cells . Inhibition of cytosolic compartment of cell proliferation at different time‐point in renal carcinoma cells were in accordance with previous reports .…”
Section: Resultssupporting
confidence: 91%
“…37 Moreover, caspase-3/ROCK1/MLC has also been proved to be a novel cyclic positive feedback loop for regulating apoptosis in different cell types, such as cardiac myocyte, human leukemia cells and neurons. [40][41][42] We have previously reported the caspase-3/ROCK1/MLC feedback loop in H 2 O 2induced PC12 cell injury, and NMMHC IIA is also involved in a positive feedback loop that links caspase-3/ROCK1/MLC signaling axis. 13,22 Our present findings confirmed that I/ R-induced caspase-3 cleavage led to decrease of ROCK1 and MLC phosphorylation.…”
Section: Discussionmentioning
confidence: 98%
“…TPL has been found to sensitize cancer cells to apoptosis [1618]. Moreover, a recent study reported that the expression of GRP78 in pancreatic cancer cell lines is downregulated by TPL, leading to cell apoptosis and autophagy [19].…”
Section: Discussionmentioning
confidence: 99%